2016
DOI: 10.1039/c5cc10582j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular level insight on the adsorption of carboxylic acids to oxide nanoparticles in aqueous solution by X-ray photoelectron spectroscopy

Abstract: We show, for the first time, the ability to follow the surface chemistry (acid-base equilibrium) of a colloid nanoparticle (AlxOy@SiO2) while simultaneously monitoring the adsorption of a solute molecule (HCOOH) from solution using in situ X-ray photoelectron spectroscopy. Based on the results of the Al 2p and C 1s spectra a mechanism is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…We rationalize the above trend through recognition of the dominant surface interaction mechanism between (hydroxylated) silica surfaces and polar-protic molecules. Such interactions are governed by surface–adsorbate hydrogen-bonding interactions, which provide not only a favorable bonding mode between protic adsorbates and surface-bound hydroxyl groups , but also a well-established means for proton exchange. Exchange interactions during the encoding periods of T 1 – T 2 correlation measurements have significant potential to bias the resulting relaxation characteristics. This concept is elucidated by considering two coupled magnetization reservoirs, M sol and M ads , which we associate with solid-bound and adsorbate-bound hydroxyl protons, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We rationalize the above trend through recognition of the dominant surface interaction mechanism between (hydroxylated) silica surfaces and polar-protic molecules. Such interactions are governed by surface–adsorbate hydrogen-bonding interactions, which provide not only a favorable bonding mode between protic adsorbates and surface-bound hydroxyl groups , but also a well-established means for proton exchange. Exchange interactions during the encoding periods of T 1 – T 2 correlation measurements have significant potential to bias the resulting relaxation characteristics. This concept is elucidated by considering two coupled magnetization reservoirs, M sol and M ads , which we associate with solid-bound and adsorbate-bound hydroxyl protons, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[68][69][70][71] In addition, the results of liquid-phase X-ray photoelectron spectroscopy (XPS) and AFM analysis were reported to analyze the protonation phenomenon and complex structure of carboxyl groups on the surface of nanoparticles, and also to analyze the adsorption of protein and its isoelectric point on solid surfaces. [72][73][74] However, the analysis of the interfacial specificity of ions and molecules at solid-liquid interfaces suffers from the limitation that measurements are very challenging due to the random motility and noise effects of molecules and ions in liquids, which is why only a few techniques such as sum frequency spectroscopy and XPS have been proposed in the last decades. 75,76 Furthermore, various studies have reported the analysis of ionic behavior at interfaces in diverse fields such as chemical/biological sensors, energy harvesting, and batteries.…”
Section: Experimental Aspectsmentioning
confidence: 99%
“…The results of interfacial characterization using traditional atomic force microscope (AFM)‐based analytical techniques such as liquid AFM and Kelvin probe force microscopy (KPFM) are continuously being reported in related fields 68–71 . In addition, the results of liquid‐phase X‐ray photoelectron spectroscopy (XPS) and AFM analysis were reported to analyze the protonation phenomenon and complex structure of carboxyl groups on the surface of nanoparticles, and also to analyze the adsorption of protein and its isoelectric point on solid surfaces 72–74 …”
Section: Scalability Of Ionovoltaic Researchmentioning
confidence: 99%
“…Such interactions are governed by surface-adsorbate hydrogen bonding interactions, which provide not only a favourable bonding mode between protic adsorbates and surface-bound hydroxyl groups, 57,58 but also a well-established means for proton exchange. [59][60][61] Exchange interactions during the encoding periods of 1 − 2 correlation measurements have significant potential to bias the resulting relaxation characteristics. This concept is elucidated by considering two coupled magnetisation reservoirs, and , which we associate with solid-bound and adsorbate-bound hydroxyl protons, respectively.…”
Section: Relaxation Acidity and Surface-adsorbate Proton Exchangementioning
confidence: 99%